ВИХОВАННЯ ДУХОВНОСТІ СТАРШОКЛАСНИКІВ ЗАСОБАМИ ХУДОЖНЬОЇ ЛІТЕРАТУРИ (Педагогіка вищої та середньої школи, 2002)
Different problems and aspects o f bringing up o f spirit among young generation in studiing Ukrainian literature are opened in this article.